Managing balanced development in India - Analysis of achieving provisions under Article 371 j for the special development of Hyderabad Karnataka - Mohammed, Moona (International Journal of Psychosocial Rehabilitation, 2024)
Addressing the regional imbalances is the biggest challenge in the management of the development. There are Regional Imbalances in development in India for a long time. Investment and efforts should be spread out evenly across various regions to ensure balanced development of the country or a state. This article traces the history of regional imbalances in India as it existed in Mughal and British period. Nanjundappa committee report (2002) empirically established regional imbalances existed Karnataka, which is a Southern state in India. In order to rectify the backwardness of the Hyderabad Karnataka region, article 317 j was inserted in the Constitution of India. This resulted in reserving certain share of jobs and educational opportunities in Educational Institutions to the persons belonging to the region. The amendment also mandated allocating certain amount of funds for the regional development board. Since inception, the board was able to utilise Rs. 2961.47 crores out of the Rs. 4621.76 crores allocated. Board was able to complete 73.82% of works approved so far. The analysis in the paper shows that considerable progress has been made in identifying and filling up the posts reserved for the regional level. Government has been allocating exclusive funds to the Regional development board. However, utilisation of the funds and completion of works needs improvement.